Antitumor bifunctional dinuclear Pt(II) complex BBR3535 forms interduplex DNA cross-links under molecular crowding conditions - Muchova, Tereza; Quintal, Susana M; Farrell, Nicholas P; Brabec, Viktor; Kasparkova, Jana (Journal of biological inorganic chemistry, 2012)
When antitumor platinum drugs react with DNA they form various types of intrastrand and interstrand cross-links (CLs). One class of new antitumor platinum compounds comprises bifunctional Pt(II) compounds based on the dinuclear or trinuclear geometry of leaving ligands. It has been shown that the DNA-binding modes of dinuclear or trinuclear bifunctional Pt(II) agents are distinct from those of mononuclear cisplatin, forming markedly more intramolecular interstrand CLs. However, at least two types of DNA interstrand cross-linking by bifunctional Pt(II) complexes can be envisaged, depending on whether the platinum complex coordinates to the bases in one DNA molecule (intramolecular interstrand CLs) or in two different DNA duplexes (interduplex CLs). We hypothesized that at least some antitumor bifunctional poly(di/tri)nuclear complexes could fulfill the requirements placed on interduplex DNA cross-linkers. To test this hypothesis we studied the interduplex cross-linking capability of a representative of antitumor polynuclear agents, namely, dinuclear Pt(II) complex [{trans-PtCl(NH(3))(2)}(2)-μ-{trans-(H(2)N(CH(2))(6)NH(2)(CH(2))(2)NH(2)(CH(2))(6)NH(2))}](4+) (BBR3535). The investigations were conducted under molecular crowding conditions mimicking environmental conditions in the cellular nucleus, namely, in medium containing ethanol, which is a commonly used crowding agent. We found with the aid of native agarose gel electrophoresis that the DNA interduplex cross-linking efficiency of BBR3535 under molecular crowding conditions was remarkable: the frequency of these CLs was 54%. In contrast, the interduplex cross-linking efficiency of mononuclear cisplatin or transplatin was markedly lower (approximately 40-fold or 18-fold, respectively). We suggest that the production of interduplex CLs in addition to other DNA intramolecular adducts may provide polynuclear Pt(II) compounds with a wider spectrum of cytotoxicity.
Keywords: interkalátory; Intercalating Agents; DNA; reagencia zkříženě vázaná; adukty DNA; nádory; Cross-Linking Reagents; Organoplatinum Compounds; lidé; protinádorové látky; organoplatinové sloučeniny; Neoplasms; Humans; DNA Adducts; Antineoplastic Agents